Pencegahan Stunting Sejak Dini di Kabupaten Enrekang - Musrayani Usman; Andi Selvi Yusni Tasari; Andi Muhammad Arif Haris; Mario Mario (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service program was carried out to improve parenting literacy in the prevention of stunting in Buntu Batu Subdistrict, Enrekang Regency, through a participatory, community-based approach. Referring to the theories of child development ecology, community empowerment, and health literacy, the activities included dialogical education, focus group discussions, door-to-door counseling, and the distribution of locally adapted educational leaflets. The “3T” model (Regular, Monitored, Involved) was developed as a household-based educational innovation to enhance collective awareness and behavioral change in families. Pre-test and post-test results showed a significant increase in participants' understanding of the definition, causes, and long-term impacts of stunting, as well as preventive strategies. This program demonstrates that contextual and relational educational approaches can effectively overcome socio-cultural barriers and reach vulnerable groups excluded from formal forums. These findings highlight the importance of strengthening local educational hubs such as Posyandu and PKK as agents of change. The implications of this initiative suggest that integrating local cultural approaches with community participation can build a healthy, sustainable, and community-rooted parenting ecosystem.